2019
DOI: 10.1021/acsabm.9b00669
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Hexagonal Boron Nitrides in Wound Healing

Abstract: There is an increased interest in the use of hexagonal boron nitrides (hBNs) in medicine due to their unique properties that include low toxicity, absorption of UV light and neutrons, high chemical stability, and mechanical strength. In this study, hBNs were investigated for wound healing therapy as a potential therapeutic agent. Boron compounds (especially boric acid) are increasingly used in wound healing therapy; however, their short half-life is a bottleneck and limits their use. Because hBNs slowly degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Angiogenesis ability of HUVECs treated with hBN showed promising results. Additionally, it was found that hBN might also improve the wound healing process by lowering ROS due to its antioxidant capacity, similarly to BA; it was found that hBN can rescue cells from apoptosis, and that at low concentrations, it did not depolarize the mitochondria nor disrupt F-actin formation ( Şen et al, 2019 ).…”
Section: Dm Coatings and Cellular Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiogenesis ability of HUVECs treated with hBN showed promising results. Additionally, it was found that hBN might also improve the wound healing process by lowering ROS due to its antioxidant capacity, similarly to BA; it was found that hBN can rescue cells from apoptosis, and that at low concentrations, it did not depolarize the mitochondria nor disrupt F-actin formation ( Şen et al, 2019 ).…”
Section: Dm Coatings and Cellular Interactionmentioning
confidence: 99%
“…Having analogous structure but insulating electrical behavior, hBN is sometimes referred to as “white graphene.” hBN features properties such as high hydrophobicity, thermal insulation, electrical insulation, low dielectric constant, resistance to oxidation, high chemical stability, and mechanical strength ( Mahvash et al, 2017 ; Chilkoor et al, 2018 ; Merlo et al, 2018 ; Emanet et al, 2019 ; Mukheem et al, 2019 ). Due to these properties, 2D BN-based materials have also demonstrated potential in antibacterial coatings ( Mukheem et al, 2019 ), as well as applications in the biomedical field – such as wound healing ( Şen et al, 2019 ), and bone tissue regeneration ( Şen et al, 2019 ; Aki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, wound healing assays were performed to determine the modulatory cellular response to RMF on wound closure efficiency. L929 and HaCaT were grown in 24-well plates at a density of 1 × 10 6 per well and were incubated for 24-h. Then, linear scratches were made in the confluent L929 and HaCaT monolayer cultures with a sterile p100 pipet tip [78,79]. Then, cells were immediately rinsed with DPBS to remove cellular debris, and images of the scratches were taken (at t = 0 h) using the digital camera (NIS Elements F Package version 4.00.06, camera Nikon DS-Fi1, Nikon, Melville, NY, USA) connected to the inverted microscope Nikon TS-100 (Nikon, Melville, NY, USA).…”
Section: In Vitro Wound Healing Assaymentioning
confidence: 99%
“…[5] Moreover, Şen et al have studied the antimicrobial activity of the hBNs for the wound healing process and found that the hBNs show the antimicrobial activity on Gram-positive and Gram-negative bacteria. [6] L-3,4 dihydroxyphenylalanine (L-dopa) has so many applications in medicine and food industry and has a phenolic structure belonging to the catecholamine family derived from tyrosine. It has been shown to be an effective scavenger of superoxide and hydroxyl radicals found naturally in all aerobic organisms.…”
Section: Introductionmentioning
confidence: 99%